Competence Between Endangered Wild Animals: an Example of Takin (Budorcas taxicolor bedfordi) and Panda (Ailuropoda melanoleuca) - Altigani, Latifa A. A.; Bu, Shuhai; Adam, A. M. A.; Si, Kaichang; Wu, Xun-tao; Li, Guochun; Song, Huadong (European Journal of Applied Sciences, 2022)
The study was conducted in tow locations are: (1) Taibai Mountain natural reserve (107°22’-107°51’E and 33°49’-34°05’N) and (2) Zhouzhi natural reserve (108° 14′-108° 18′ E, 33° 45′-33° 50′ N). To examine and analyze the impact of Golden takin behavior on the Giant panda activity in winter habitat and analyze their interactions at Taibai Mountain and Zhouzhi natural reserve. For habitat survey, randomly walked within the study areas with different vegetation types to search for signs of each species. The presence of Golden takin and Giant panda was identified based on their fresh droppings. Once fresh droppings were found and a sampling plot of 20 m x 20 m was established and centered on the droppings location. Two (2 m × 10 m) were set at different locations within the 20 m × 20 m plot, and observations were made according to the type of habitats including type of trees, bamboo type, bamboo cover, bamboo density, canopy, shrub cover and herb cover. At Taibai Mountain, a total of 12 infrared cameras were placed on tree stems at 1 m height, the laying density of cameras is 4 sets / km2 and other 20 infrared cameras were mounted at Guangtoushan in Zhouzhi natural reserve,to monitor Golden takin and Giant panda movement. Camera traps data were collected every three months depending on the status of battery and the weather conditions. Takin displayed the highest peak activity at periods of 16:00-18:00 pm (48.03%) and 16:00-18:00 pm (39.29%) in 2013-2014 and 2014-2015, respectively, while for Panda the highest peaks of activity were recorded at periods of 14:00-16:00 pm (24.58%) and 12:00-14:00 pm (26.13%) in 2013-2014 and 2014-2015, respectively. At Zhouzhi natural reserve, Takin showed also highest peak of activity at periods of 16:00-18:00 pm (23.48%) and 16:00-18:00 pm (38.48%) in 2014-2015 and 2015-2016, respectively, whereas the highest peak activity for Panda were recorded at periods of 12:00-14:00 pm (19.15%) and 12:00-14:00 pm (18.22%) in 2014-2015 and 2015-2016, respectively.